Cell death induction by the acute promyelocytic leukemia-specific PML/RARα fusion protein - Ferrucci, Pier Francesco (The National Academy of Sciences of the USA, 1997)
PML/RARα is the abnormal protein product generated by the acute promyelocytic leukemia-specific t(15;17). Expression of PML/RARα in hematopoietic precursor cell lines induces block of differentiation and promotes survival. We report here that PML/RARα has a potent growth inhibitory effect on all nonhematopoietic cell lines and on the majority of the hematopoietic cell lines tested. Inducible expression of PML/RARα in fibroblasts demonstrated that the basis for the growth suppression is induction of cell death. Deletion of relevant promyelocytic leukemia (PML) and retinoic acid receptor (RARα) domains within the fusion protein revealed that its growth inhibitory effect depends on the integrity of the PML aminoterminal region (RING, B1, B2, and coiled coil regions) and the RARα DNA binding region. Analysis of the nuclear localization of the same PML/RARα deletion mutants by immunofluorescence and cell fractionation revealed that the biological activity of the fusion protein correlates with its microspeckled localization and its association to the nuclear matrix. The PML aminoterminal region, but not the RARα zinc fingers, is required for the proper nuclear localization of PML/RARα. We propose that the matrix-associated microspeckles are the active sites of PML/RARα and that targeting of RARα sequences to this specific nuclear subdomain through PML sequences is crucial to the activity of the fusion protein on survival regulation.